Ancient Craton‐Wide Mid‐Lithosphere Discontinuity Controlled by Pargasite Channels - Z. J. Sudholz; P. Zhang; C. M. Eakin; G. M. Yaxley; A. L. Jaques; C. Frigo; K. Czarnota (Geophysical Research Letters, 2024)
Abstract The mechanisms governing a commonly observed seismic velocity drop in the cratonic lithosphere, referred to as the mid‐lithospheric discontinuity (MLD), have been widely debated. To identify the composition and seismic structure of MLDs, we have analyzed Sp receiver functions (SRF) and mantle xenocrysts for six regions across Australia. We utilize locations where seismic stations and kimberlite‐hosted mantle xenocrysts are both available, allowing for comparison between seismological and petrological constraints. Our results show negative SRF phases indicative of the MLD coincide with clinopyroxene‐depleted zones at 60–140 km depth. Clinopyroxenes with different chemical compositions across the MLD define a litho‐chemical discontinuity. Modeling and experimental data show that MLDs may be explained by modified lherzolite with 10%–20% modal pargasite. Pargasite MLDs may form when rising H2O‐bearing melts cross the amphibole dehydration curve and react with clinopyroxene in lherzolite. Because the amphibole dehydration curve is isobaric at 80–120 km, pargasite will be precipitated as horizontal channels.